A randomized, double-blind, placebo-controlled, dose-response study to assess the pharmacokinetics, efficacy, and safety of gabapentin enacarbil in subjects with restless legs syndrome - Lal, Ritu; Ellenbogen, Aaron; Chen, Dan; Zomorodi, Katie; Atluri, Harisha; Luo, Wendy; Tovera, James; Hurt, Janet; Bonzo, Daniel; Lassauzet, Marie-Liesse; Vu, Amanda; Cundy, Kenneth C (Clinical neuropharmacology, 2012)
The objective of this study was to determine steady-state gabapentin exposures and corresponding relief of symptoms and safety profile produced by 4 dose levels of gabapentin enacarbil (GEn) in subjects with restless legs syndrome (RLS). Subjects with RLS (n = 217) were randomized to receive once-daily, orally administered GEn 600 (n = 48), 1200 (n = 45), 1800 (n = 38), or 2400 mg (n = 45) or placebo (n = 41) in this 12-week, double-blind, multicenter study (NCT01332305). Clinic visits were at screening, baseline, and weeks 1, 2, 3, 4, 6, 8, 10, and 12; plasma gabapentin concentrations were measured by a validated liquid chromatography-mass spectrometry/mass spectrometry method at weeks 4 and 12. Exposure to gabapentin was proportional to GEn dose. Time to maximum plasma concentration was 7 to 9 hours, and elimination half-life was ~6 hours. The mean reduction from baseline to week 12 in International Restless Legs Syndrome Rating Scale total score and proportions of subjects with "much improved"/"very much improved" Clinical Global Impression-Improvement scores (investigator and patient ratings) ranged from -12.9 to -13.9 for GEn treatment groups versus -9.3 for placebo. The 2 most commonly reported adverse events were somnolence and dizziness. Gabapentin exposure was approximately proportional to GEn dose. Efficacy data showed that a once-daily dose of GEn 600 to 2400 mg provides greater relief of RLS symptoms than placebo; GEn was generally well tolerated with an adverse event profile consistent with gabapentin.